Variation in location of the distobuccal root canal in a permanent maxillary second molar: A case report - Anisha Mishra; Velmurugan Natanasabapathy; Dinesh Kowsky; Jitendra Sharan; Anand Marya (Clinical Case Reports, 2023)
Key Clinical Message Clinicians should be aware of the variations in the number of roots and root canals and the peculiar or eccentric location of root canals. An intraoperative CBCT can be very useful in improved visualization of the anatomical variations. Abstract This case report describes the unusual location of the distobuccal root canal in a maxillary second molar with root fusion. On access opening, three distinct root canal orifices, the mesiobuccal canal, palatal canal, and a third orifice closer to the palatal canal, were seen, giving an illusion of an additional palatal canal. An attempt was made to search for the distobuccal canal in its usual position, leading to the gouging of the pulp chamber floor. An intraoperative limited field of view cone‐beam computed tomography (CBCT) revealed the root orifice adjacent to the palatal canal was the distobuccal canal. CBCT also revealed fusion of both the buccal and palatal roots in the root's coronal and middle third region, but they were not fused apically.